2016
DOI: 10.4172/2471-9455.1000113
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Impact of Tinnitus Perception on the Quality of Life

Abstract: Purpose: the aim of this study is to assess the impact of tinnitus perception on the quality of life of tinnitus sufferer's. Materials and methods:34-tinnitus sufferers were recruited in this study with a wide range of hearing loss thresholds (HLT) and tinnitus severity status. Pure tone air conduction audiometry was performed to assess the hearing level of the participants in this study. Anxiety and depression were assessed in this study using the hospital anxiety and depression scale (HADS). Tinnitus severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…In agreement with our study, Erlandsson and Holgers [26] and Alhamzi et al [27] found that no significant difference in the severity of tinnitus based on THI score according to gender difference.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our study, Erlandsson and Holgers [26] and Alhamzi et al [27] found that no significant difference in the severity of tinnitus based on THI score according to gender difference.…”
Section: Discussionsupporting
confidence: 93%
“…Alhazmi et al [27] found that nearly two-third of the patients in their study with tinnitus had some degree of hearing loss, whereas one-third had normal hearing. Also, they assessed the influence of tinnitus perception on the quality of life using THI and Tinnitus Functional Index questionnaires.…”
Section: Discussionmentioning
confidence: 87%
“…and the authors reflected the feedback accordingly in the final version of the questionnaire. 'Handedness' is also discussed in many tinnitus literatures [12,[30][31][32] and was evaluated to be included for the tinnitus outcome questionnaire for sound management. In the domain of 'Tinnitus management,' all questions were evaluated to be appropriate except one question about medication ('Are you currently taking any medications?')…”
Section: Discussionmentioning
confidence: 99%
“…This significant correlation has also been found in tinnitus patients. 29 There is no clear understanding of the pathological and physiological mechanism of age-related hearing loss.…”
Section: Discussionmentioning
confidence: 99%